The role of a pedagogue in the advancement of teaching in a contemporary school - Kakuk, Sara (Array, 2020)
An expert associate pedagogue is a key carrier of the developmental-pedagogical activity in a school. The aim of this activity is to foresee, design, encourage, and guide the development of the educational activity of a school for the purpose of synchronizing the needs of students and their developmental potentials. A pedagogue’s area of work is extremely large. It refers to attendance in all areas of the developmental-pedagogical process, starting with planning and programming and goes all the way to the evaluation of the achieved results. Also, the pedagogue has an important role in the advancement of the developmental-pedagogical process, from monitoring the educational process to organizing professional development and implementation and encouragement of active research. Monitoring the developmental-pedagogical process refers to monitoring the achievements of developmental and educational plans and programs and the quality of monitoring the same, monitoring of the actualization of extracurricular activities and the direct actualization of the developmental-pedagogical process. Professional development modernizes the knowledge of the teachers which they gained during the beginning of their education and perfects their professional skills. The role of the pedagogue is to encourage teachers and motivate them for active research with which teachers solve perceived problems and advance their practice towards the set goals. Using theoretical analysis, this paper will give an overview of certain areas of a pedagogue’s methods in teaching and school with an emphasis on more contemporary context. The aim of this paper is to provide an insight into certain areas of action of an expert associate pedagogue, which are in service of improving the educational process of a contemporary school.